Which factors impact on quality of life for adults with blepharospasm and hemifacial spasm?. (4th March 2021) - Lawes-Wickwar, Sadie; McBain, Hayley; Hirani, Shashivadan P.; Hurt, Catherine S.; Dunlop, Nicola; Solly, Dianne; Crampton, Bridget; Newman, Stanton P.; Ezra, Daniel G.
ABSTRACT: Purpose : Benign essential blepharospasm (BEB) and hemifacial spasm (HFS) are debilitating conditions causing spasms to the eyes and/or face and can significantly impact on quality of life (QoL). Initial research has highlighted potential factors impacting on QoL in BEB, but there remains a wealth of demographic, clinical, and psychosocial factors that may contribute to QoL but have not received attention. Methods : Cross-sectional baseline data were collected before a single-masked randomised controlled trial from 130 adults with BEB and HFS recruited from botulinum toxin clinics at Moorfields Eye Hospital, London. QoL was measured using the 24-item Craniocervical Dystonia Questionnaire (CDQ24), which provides a total score and five subscale scores relating to Stigma, Emotional state, Pain, Activities of daily living (ADL), and Social/family life . Treating clinicians provided clinical data. Hierarchical multiple regressions were performed on this baseline data to identify significant predictors of QoL. Results : ADL and Stigma were the areas most impacted upon whilst patients experienced better adjustment in relation to Pain, Social/family life, and Emotional state. CDQ24 Total scores were explained by the model (80% variance) and were significantly associated with appearance concerns, emotional representations, perceived negative consequences of the condition, mood, and dose of botulinum toxin. Conclusions : Patients with BEB and HFS report a detrimental impact on ADL and perceived stigma in relation to their condition. Predominantly, individual perceptions and mood are associated with QoL in this population, rather than demographic and clinical factors, signifying areas to target in the design of future healthcare services or interventions.